METODE DAN TEKNIK PERENCANAAN PENDIDIKAN ISLAM - Mansur Mohammad; Yahya Ashari Muhammad (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2025)
This research tries to explain educational planning methods and techniques. The method used in this research is qualitative with a normative analytical descriptive approach adapted to library sources. Meanwhile, the research object discusses planning methods and techniques in education in general and in Islamic educational institutions in particular. As we already know, planning in an educational institution, of course, cannot deviate from the educational objectives themselves, because these objectives will later become the starting point for preparing a planning framework. And so that planning in an educational institution does not deviate from educational goals, appropriate and appropriate planning methods and techniques must be used